Evolution Pattern of Flash Drought in Hanjiang River Basin and Its Response to Middle Route of South-to-North Water Transfer Project - HUANG Kai; DUAN Kai (Renmin Zhujiang)
By identifying flash drought events in the Hanjiang River Basin, the differences in the characteristics of flash drought events before and after the implementation of the Middle Route of the South-to-North Water Transfer Project were analyzed. Moreover, three machine learning methods, partial least squares regression (PLSR), support vector machine (SVM), and random forest (RF), were employed to establish regression models for the duration of flash droughts, and the impact of the Middle Route of the South-to-North Water Transfer Project on the duration of flash droughts was quantitatively analyzed. The results indicate that: ① After the implementation of the Middle Route of the South-to-North Water Transfer Project, the frequency of flash droughts in the Hanjiang River Basin increased from an average of 0.7 times per year to 0.9 times, and the duration of flash droughts increased from an average of 24.6 days per year to 34.5 days. However, spatially, the duration of flash droughts significantly extended in the upper reaches. The increase in the middle reaches weakened, and the duration of flash droughts in the lower reaches shortened. ② The spatial distribution of flash drought onset durations evolved from uniform distribution of 5~6 days to uneven distribution between the upper and lower reaches, with durations shortening to 3~5 days in the upper reaches and extending to 7~9 days in the middle and lower reaches. ③ The RF model demonstrated the best simulation performance for flash drought duration. Climatic conditions had the most significant impact on flash drought duration, with a relative importance of 0.34. Among them, precipitation accounted for 0.14, net radiation for 0.12, and relative humidity for 0.08. The Middle Route of the South-to-North Water Transfer Project extended the duration of flash droughts in the middle and lower reaches of the Hanjiang River Basin, with a relative importance of 0.12.